A Systematic Review of Open and Minimally Invasive Surgery for Treating Recurrent Hallux Valgus - Nair, Arun; Bence, Matthew; Saleem, Jawaad; Yousaf, Azka; Al-Hilfi, Lena; Kunasingam, Kumar (The Surgery Journal, 2022)
Background Despite advancements in primary correction of hallux valgus (HV), significant rates of reoperation remain across common techniques, with complications following primary correction up to 50% according to some studies.1 This study explored different methods of surgery currently used in treating HV recurrence specifically (for which literature on the subject has been limited), evaluating open and adapted minimally invasive surgical (MIS) primary techniques used for revision.Methods In December 2020, literature search for both open and MIS surgical techniques in HV revision was conducted using PubMed, EMBASE, and MEDLINE library databases.Results and Conclusion Of initial 143 publications, 10 were finally included for data synthesis including 273 patients and 301 feet. Out of 301 feet, 80 (26.6%) underwent revision with MIS techniques (involving distal metatarsal osteotomies). Those undergoing grouped MIS revisions had an average improvement of 38.3 in their American Orthopaedic Foot and Ankle Society score, compared to 26.8 in those using open techniques. Revision approaches using grouped MIS techniques showed a postoperative reduction in intermetatarsal angle and HV angle of 5.6 and 18.4 degrees, respectively, compared to 15.5 and 4.4 degrees, respectively, for open techniques. There are, however, limitations in the current literature on MIS techniques in revision HV surgery specifically. MIS techniques grouped did not show worse outcomes or safety concerns compared to open techniques.
Keywords: MIS; minimally invasive hallux valgus; bunion surgery; revision hallux valgus